2007
DOI: 10.1021/jp0765805
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Characterization of the Photochemically Interconvertible Side-On and End-On Bonded Dioxygen−Iron Dioxide Complexes in Solid Argon

Abstract: Two interconvertible iron dioxide-dioxygen complexes were prepared and characterized by matrix isolation infrared absorption spectroscopy as well as theoretical calculations. Iron atoms react with O2 to form the inserted FeO2 molecule in solid argon only upon UV-visible light irradiation. Annealing allows the dioxygen molecules to diffuse and to react with FeO2 and form the side-on and end-on bonded dioxygen-iron dioxide complexes, (eta2-O2)FeO2 and (eta1-O2)FeO2. The side-on bonded structure is a peroxide com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 43 publications
1
64
0
Order By: Relevance
“…[95,106] Furthermore,m any of the monoxides and dioxides have been found to add furtherO 2 units. Complexes MO(O 2 )o ft he monoxides MO with one O 2 ,m ostly with side-on coordination, have been observed for M = Sc, [45,46] Y, [47] La, [47] Ti, [56] Zr, [57] Hf, [57] Mn, [70] Fe, [73,76] Ni, [91] Pt, [92] and likelya lso for Co [80] and Rh. [81] For Ti,t he TiO(O 2 ) 2 complex is also observed.…”
Section: Generation Of Mo Clusters In Matricesmentioning
confidence: 97%
See 2 more Smart Citations
“…[95,106] Furthermore,m any of the monoxides and dioxides have been found to add furtherO 2 units. Complexes MO(O 2 )o ft he monoxides MO with one O 2 ,m ostly with side-on coordination, have been observed for M = Sc, [45,46] Y, [47] La, [47] Ti, [56] Zr, [57] Hf, [57] Mn, [70] Fe, [73,76] Ni, [91] Pt, [92] and likelya lso for Co [80] and Rh. [81] For Ti,t he TiO(O 2 ) 2 complex is also observed.…”
Section: Generation Of Mo Clusters In Matricesmentioning
confidence: 97%
“…[56] For Sc, Y, and La, ozonide complexes MO(O 3 )h ave also been generated. [48,49] Complexes MO 2 (O 2 )o ft he dioxides MO 2 with one O 2 have been found for M = V, [58,60] (tentatively Cr, [66] )M n, [70,72] Fe, [73,76,78] Co, [84] Ni, [91] Zn, [104] Nb, [59,61] Mo, [65] Ru, [71] Rh, [81] Cd, [104] La, [49] Ta , [59,61] W, [66] Re, [71] Os, [71] and Ir, [82,87] mostly with side-on coordinated O 2; and in somec ases with end-on coordination. For example, iron atoms react by UV/Vis irradiation with O 2 to yield the FeO 2 dioxide, which by annealinga ttaches another O 2 to form the FeO 2 (O 2 )c omplex.…”
Section: Generation Of Mo Clusters In Matricesmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Beyond these anionic complexes, neutral iron oxides, such as [O 2 Fe(h 2 -O 2 )], have been stabilized under cryogenic conditions in rare gas matrices. [4] Furthermore, iron nitrido complexes in the + 5 and + 6 oxidation states have been successfully prepared in solution at low temperatures, as shown by Mçssbauer and X-ray absorption spectroscopy. [5,6] Despite a long history of research in this field, only a few binary iron halides are known.…”
mentioning
confidence: 99%
“…Note that both the observed OÀO stretching frequency and the predicted OÀO bond length suggest that the O 2 ligand in complex B is due to a peroxide dianion with an OÀO single bond. [42,43] Previous experimental studies on the adsorption of water and molecular oxygen on single-crystal platinum surface showed no evidence for the cleavage of H 2 O upon adsorption, and the presence of molecular oxygen has no influence on water adsorption process. [44] Consistent with the results from surface chemistry studies, the platinum atoms were found to be inert toward water molecule in solid argon, and no water dissociation product was detected in the reaction of platinum atoms and H 2 O in the presence of O 2 .…”
Section: Reaction Mechanismmentioning
confidence: 99%